Dataflow computing models, languages, and machines for intelligence computations - Herath, J.; Yamaguchi, Y.; Saito, N.; Yuba, T. (IEEE Transactions on Software Engineering, 1988)
The authors compare dataflow computing models, languages, and dataflow computing machines for numerical and nonnumerical computations. The high-level-language-graph transformations that must be performed to achieve high performance for numerical and nonnumerical programs executed in a dataflow computing environment are described for Lisp, using the DCBL transformations. Some general problems of dataflow computing machines are discussed. Performance evaluation measurements obtained by executing benchmark programs in the ETL nonnumerical dataflow computing environment, the EM-3, are presented.< >